The workshop of being: religious affections and their pragmatic valuein the thought of Jonathan Edwards and William James - Campagna-Pinto, S. T. (Lexington Books, 2011)
The sacred trace -- A new reach of freedom -- Heart religion and the pragmatist imagination -- The art of expansiveness -- Strenuous democracy and the workshop of being